Limitation period of action for specific performance in contract of sale of land: Revisited - Md Dahlan, Nuarrual Hilal (2007)
In all legal systems based on common law, limitation period play an important part in all of its civil actions.Any failure on part of the litigating parties to commence legal action in court within the stipulated limitation period, would, instead, bar the legal action instituted.The limitation period for all actions founded on contract pursuant to section 6 of the Limitation Act 1953 is 6 years.However, based on the decided case-law, the limitation period for action of specific performance of a contract of sale of land, notwithstanding this action is unequivocally founded on contract,is 12 years,not 6.This is because all actions for specific performance of contract of sale of land were and are considered in the decided case-law to be actions 'to recover land'. On the other hand, pursuant to section 9 of the Limitation Act 1953, all actions for recovery of land, their limitation period is 12 years.However, in the author's view, the limitation period of action for specific performance of contract of sale and purchase of land should, instead of being 12 years, be 6 years as well.This is because, This is because, this action too is an action founded on contract.However, this contention is to the contrary of the judgments decided in certain reported case-law.This paper examines these cases vis-a-vis the related statutory provisions and provides for the grounds supporting the contrary contention of certain learned legal author respecting the limitation period of specific performance for contract of sale of land.This paper will unveil and study the grounds and policies of the concerning the issue.